PEDAGOGICAL APPROACH TO THE TEACHER-STUDENT RELATIONSHIP IN POLISH SECONDARY EDUCATION (Studies in Comparative Education, 2023)
The work of a teacher at the school stage is a special kind of work, which is inextricably linked to what is so accurately described as "love of human souls". School is one of the first social institutions outside the family with which a child comes into contact in everyday life. The extremely dynamically developing reality, civil and information societies, formulate new expectations, pose new challenges, which in many aspects, and perhaps above all, concern education new generations of people equipped with the ability to cope with such a complicated reality. These challenges in the initial phase should be met by well-prepared teachers. These are primarily challenges for modern pedeutology, for well-prepared educators, for educational leaders. The article presents the findings from a survey with Polish lyceum students as to what personality traits should an ideal teacher possess; what is the teacher's attitude to the student's opinion; how often teachers have conversations with students about the students’ interests. The findings demonstrate some inconsistences in the society understanding the teacher’s role and the place of teachers and students in it. The students see their ideal teacher as a combination of positive traits of character which is hardly possible in real life conditions. When students speak about the existing situation, they demonstrate that teachers tend to underestimate their point of view and attach little importance to students’ interests. That brings about the situation when both students and teachers are not ready to trust each other to the extent that they can become agents of change in transforming education.